CFD Simulation and Experimental Study of Inverted-Umbrella Aerators in a Stirred Tank - Yuxian Hu, Tao Sun, Hongyin Xu, Gaiqiang Yang, Dongdong Jia (Design Engineering, 2020)
The hydrodynamic characteristics of the fluid in the lab scale stirred tank, which stirred by inverted-umbrella aerators with different structures is evaluated by using the Computational Fluid Dynamics (CFD) model.K-ε models are used for the turbulence fluid in the tanks. Experiments are performed in the tank with the Particle Image Velocimetry (PIV). Comparing with PIV experiment data, the reliability of the methods in this paper are verified.The negative pressure zones and the turbulent kinetic energy of the aerators have been investigated. The values of turbulent kinetic energy in the stirred tank are changed significantly near the aerators. The structure of the aerators is the greatest impact on the flow rate, especially for the vortexes. High-turbulence aerators can cause many vortexes, which can fully mix the gas-liquid.